Bhramari Pranayama: A Non-Pharmacological Approach Against Current Coronavirus Disease 19 Pandemic - Nisha Garg; Srikanta Kumar Panda (International Journal of Ayurveda and Pharma Research, 2021)
Objective: For maintaining sound physical and mental health it is extremely beneficial for mankind to do pranayama. Prāṇāyāma bring about varying physiological and psychological effects. Pranayama is a branch of yoga practice and also considered as the fourth limb of ancient aṣṭāṅga yoga consisting of breathing techniques. This article aims to attain an insight on the effectiveness of Bhramari Pranayama (Bhr.P) on health and explores its need to be implemented in day to day life as a routine by all individuals in current covid 19 pandemic.Data source: The studies done in previous years were found using Medline, Embase, Google scholar, pub med and manual search. Studies conducted on the health effectiveness of Bhramari Pranayama specifically were included in this study.Review methods: It has been tried to keenly understand the role of Bhramari pranayam in particular and exploring some new concepts related to it in this review. Features of Bhramari Pranayama are dealt in detail with its potential effects on various systems of human body and its potentiality as a therapy tool.Result and conclusion: In the studies incorporated, the Bhramari pranayam practices have shown para-sympathetic dominance. There are some uplifting effects of Bhramari pranayam on different physiological systems. In holistic yoga therapy schedule pranayama is also an integral component which involves slowing down of the normal breathing rate along with an internal awareness and conscious inner focus on the respiration and reduces stress which finally causes improvement in ailments due to covid 19 pandemic.